Ship and Offshore Structure Design in Climate Change Perspective - Bitner-Gregersen, Elzbieta Maria; Eide, Lars Ingolf; Hørte, Torfinn; Skjong, Rolf (SpringerBriefs in Climate Studies, 2013)
This book summarizes results of longstanding research and scientific contributions from many projects and relevant working groups. It collects and evaluates wind and wave climate projections under changing climate having design needs and marine safety in focus. Potential impact of projected climate change in met-ocean conditions on ships and offshore structures is discussed and illustrated by an example of the expected wave climate change on tanker design. The monograph is intended for students, researchers and industry based engineers who want a summary of the many studies that have been carried out on climate change effects on wind and waves and their importance for design and operations of ship and offshore structures. The reader needs only a moderate knowledge of marine wind and wave climate to follow the text.